Battered Child Syndrome; a Case Study - Pezeshki, Arastoo; Rahmani, Farzad; Ebrahimi Bakhtavar, Hanieh; Fekri, Sanaz (Archives of Academic Emergency Medicine, 2018)
One of the important and usual missed causes of pediatric traumas is child abuse. This ominous phenomenon, which can be presented physically, psychologically, sexually, and emotionally has grown significantly in recent years. Many children are not diagnosed in the early stages of evaluation. Battered Child Syndrome is used to describe the clinical condition of the child serious physical abuse by parents or caregivers. Medical staff should always keep the syndrome in their mind for those brought to the emergency department with trauma. In this report, we described a patient complained of dysphagia following a falling from a height and multiple epidural hematomas and final diagnosis of battered child syndrome.